PENGARUH RATIO PROFITABILITAS TERHADAP HARGA SAHAM PADA BANK MILIK PEMERINTAH ( BUMN ) YANG TERDAFTAR DI BURSA EFEK INDONESIA ( BEI ) PERIODE 2007-2014 - Lola Devita Sari; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This reasearch aimed to analyze the influence of the profitability ratio on stock prices at state-owned bank (BUMN) listed on the Indonesia Stock Exchange (BEI) in the period of 2007-2014. This research used financial ratio analysis, it was profitability ratio which was analyzed by using the variables of profitability itself, they were : Return on Assets (ROA) Return on Equity (ROE), Net Profit Margin (NPM), and Earnings per Share (EPS). The method used to observe the effect of the profitability ratio on stock prices was simple linear regression of statistical analysis. The results of this research indicate that ROA does not have a significant effect on stock prices, and variabel of ROE, NPM, EPS have a significant effect on stock prices.Keywords : Profitability Ratio, Stock Prices, ROA, ROE, NPM, EPS